Is yield pressure at the cardia increased by effective fundoplication?. Issue 10 (October 1989) - McGouran, R C; Galloway, J M; Wells, F C; Hendrie, O R
Abstract : Yield pressure at the cardia was measured before and after fundoplication in 10 patients; five had a Nissen fundoplication and five a Belsey mark IV procedure. Surgery was considered successful if oesophagitis healed or if 24 hour pH monitoring returned to normal. There was a marked rise in yield pressure in all eight patients with a successful operation. Yield pressure remained low in two patients in whom oesophagitis persisted.